Tradisi dan inovasi dalam kursus ulum hadith: Analisis terhadap penerimaan pelajar Institusi Pengajian Tinggi Swasta (IPTS) - Khalilullah Amin, Ahmad (2023)
The teaching and learning methodology (P&P) in Ulum hadith scholars is usually applied traditionally since the existence of this discipline in the tabi'in era. However, the advancement of digital technology has prompted innovation in teaching methodology, including hadith studies in higher education institutions (IPT). Nonetheless, the growth of digital technology has sparked innovation in teaching methodology, including hadith studies at higher education institutions (IPT). The transformation of technology in education has impacted lecturers’ teaching methodology, lesson content, teaching aids and students’ learning methods. This study aims to identify the traditional and innovative methods of teaching and learning as well as analyse the level of understanding and acceptance of students involving the aspects of context, input, process and product in the evaluation of a hadith course based on the Context-Input-Process-Product (CIPP) Model presented by Stufflebeam in 1968. Data was collected through interviews, observation and document analysis involving 13 lecturers and 18 students from three IPTS in North Malaysia. The data were analysed using ATLAS.ti version 8 software, content analysis and comparative methods. The results of the study found that implementing Ulum Hadith course from the context dimension is compatible with the objectives of the CLO course. From the input dimension, the facilities such as the library and lecture rooms as well as the lecturer's pedagogical knowledge and mastery of hadith studies are in good condition. The process dimension demonstrates that teaching and learning implementation, monitoring, evaluation, and connection between lecturers and students are all in good condition. The utilisation of teaching aids and lecturers' cooperation with administrators is moderate. From the product dimension, the aspects of impact, effectiveness, sustainability and transferability are positive. The study’s findings indicate a need for in-service training to improve lecturers' competence. Students’ mastery of hadith needs to be improved as well. The findings of this study could assist lecturers in improving the quality of their teaching and learning. Increasing the level of competency in teaching and learning methodology can help address the issue of lecturer incompetence while facilitating student acceptance more effectively.